Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given $K(0) = 0,\!2P$. I'm supposed to solve the ODE

$$ \frac{dK}{dt} = \lambda(P-K)$$

I have tried to seperate and integrate both sides

$$ \int \frac{1}{P-K} dK = \int \lambda \space dt$$

to get

$$\ln(P-K) = \lambda t + C$$

and then solve for $K$

$$ e^{\ln(P-K)} = P-K=e^{\lambda t + C}$$ $$ -(-K) = -(-P + e^{\lambda t + C})$$ $$ K = P - e^{\lambda t + C}$$

is that about right for the general solution? And where I'm really stuck is how do I proceed to find the particular solution?

share|cite|improve this question
$\ln (P - K) = \lambda t + C$ should be $- \ln (P - K) = \lambda t + C$. – glebovg Oct 31 '12 at 0:14
up vote 2 down vote accepted

Note that $\ln (P - K) = \lambda t + C$ should be $- \ln (P - K) = \lambda t + C$ because you need to use the substitution $u = P - K$ so that $du = - dK$. To find the particular solution use the initial data. Set $t = 0$ and $K = 0.2P$ to solve for $C$, since $K(0) = 0.2P$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.